The potential of wastewater-based epidemiology as surveillance and early warning of infectious disease outbreaks - Mao, Kang (Curr Opin Environ Sci Health, 2020)
Infectious diseases caused by pathogens have become one of the main threats to public health. Efficient monitoring of infectious disease transmission is critical to prevent and manage infectious disease epidemics. Wastewater-based epidemiology (WBE) is an efficient approach with great potential for early warning of infectious disease transmission and outbreaks. By analyzing infectious disease biomarkers in wastewater taken from wastewater collection points, the transmission of infectious diseases in certain areas can be comprehensively monitored in near real time. This short review presents WBE as a surveillance and early warning system for infectious disease outbreaks regarding pathogens with pandemic potential. We also discuss the challenges and perspective of WBE in infectious disease surveillance and early warning.